DIFUZIA PUTERII DE LA ACTORII STATALI LA CEI NON-STATALI - Octavian-Alexandru-Ștefan BROȘTEANU (Intelligence și Cultura de Securitate)
The diffusion of power in world politics has brought a lot of changes, regarding the importance of non-state actors on the global stage. It is a new phenomenon, amplified by the spread of the Internet and the technological revolution, and has in the foreground that states are losing control of certain aspects of everyday life, their place being taken by non-state organizations. These new actors take advantage of the fact that you no longer have to be "great" to be relevant on the international stage, thus foreshadowing a series of conflicts between states and non-state organizations for the coming decades. Since the national security of a state remains a duty of the intelligence services, this topic can represent a starting point for the development of other scientific writings, given the fact that, in Romania, the subject of power diffusion is little addressed. Specifically, the case study method will be used, analysing terrorist organizations, cross-border criminal organizations, hackers/hacktivists, respectively the so-called "empowered individuals" and the street movements they can cause. The results want to underline that, apart from more or less conventional conflicts between the states, non-state actors can also represent a risk factor, or even a threat, to their security. Considering that some of the non-state actors benefit from the support of the population, then all those who look after ensuring national security must pay more attention on them, to prevent negative events. In conclusion, states must be aware of the fact that they are no longer the only entities benefiting from power resources. Of course, we cannot talk about an equalization of power between state and non-state actors. However, we must all be aware of the role, both positive, but especially destructive, that non-states can have, it being a mistake to consider that the national security of the state can only be disturbed by conventional risks and threats.